Early literacy instruction for first-grade students at-risk for emotional and behavioral disorders - Balluch, Felicity Marie (Kansas State University, 2016)
This study investigated the effectiveness of an early literacy program for first grade students classified as at-risk for emotional and behavioral disorders, who were nonresponsive to previous schoolwide interventions, and who performed in the bottom one-third of their class on a standardized reading assessment. This study, which consisted of a multiple-probe across intervention groups experimental design aimed to produce literacy and behavior results previously obtained by other well-known researchers. Results indicated growth in oral reading fluency for all five participants, in nonsense word fluency for four out of the five participants, and a decreased display of total disruptive behaviors for all. Findings reaffirm outcomes obtained in previous investigations; specifically, improved early literacy skills are concomitant with ongoing decreases in disruptive classroom behavior. Limitations are discussed and suggestions for future research are provided.
Keywords: Nonsense word fluency; Literacy; Emotional disorders; Behavior disorders; Multiple probe design; Oral reading fluency